2020
DOI: 10.7150/jca.46871
|View full text |Cite
|
Sign up to set email alerts
|

Personalizing prognostic prediction in early-onset Colorectal Cancer

Abstract: Accurately estimating prognosis based on clinicopathologic variables could improve risk stratification for patients with early-onset colorectal cancer (EOCRC). Our primary goal was to create and validate a survival nomogram with adequate performance for predicting overall survival (OS) in patients with EOCRC. Least absolute shrinkage and selection operator (LASSO) Cox regression analysis was applied to identify clinical features statistically related to OS. Then we established and internally validated a surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
(50 reference statements)
1
7
0
Order By: Relevance
“…Our study demonstrated that sex had a minor influence on prognosis. These results are in accord with three studies ( 20 , 22 , 25 ) indicating that male EO-CRC patients exhibited slightly poorer survival compared to their female counterparts. However, several studies ( 13 , 15 , 16 , 18 , 19 , 24 ) indicated that sex was not a significant prognostic factor for the survival of EO-CRC patients.…”
Section: Discussionsupporting
confidence: 92%
“…Our study demonstrated that sex had a minor influence on prognosis. These results are in accord with three studies ( 20 , 22 , 25 ) indicating that male EO-CRC patients exhibited slightly poorer survival compared to their female counterparts. However, several studies ( 13 , 15 , 16 , 18 , 19 , 24 ) indicated that sex was not a significant prognostic factor for the survival of EO-CRC patients.…”
Section: Discussionsupporting
confidence: 92%
“…2 The 5-year overall survival rate for PNETs in early stages are 61.9%, and the 5year survival rate for advanced cancers is less than 20%. 3 Previous studies have found that there are differences in clinical characteristics and prognosis between young and old in cancer patients including lung cancer, 4 colorectal cancer, 5 and so on. PNETs is a kind of highly heterogeneous tumor, however, the clinical characteristics and prognosis of young patients with PNETs had not been well studied.…”
Section: Introductionmentioning
confidence: 99%
“…SUMOylation of METTL3 regulating its m 6 A RNA methyltransferase activity (Du et al , 2018). Liu et al (2019) found that high METTL3 expression and decreased regulation of METTL14, FTO and ALKBH5 were positively correlated with poor prognosis in colorectal cancer (CRC) patients.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence have supported the fact that the m 6 A RNA methylation impact the initiation and progression of human cancers through diverse mechanisms, such as acute myeloid leukemia, bile duct carcinoma, glioblastomas and hepatocellular carcinoma (Dai et al , 2018; Jaffrey et al , 2017; Wang et al , 2017). The m 6 A modification is reversible and dynamic, involving adenosine methyltransferases (m 6 A writers), RNA-binding proteins (m 6 A readers) and demethylases (m 6 A erasers), which can add, recognize or remove m 6 A-modified sites and alter important biological processes accordingly (Pinello et al , 2018; Liu et al , 2019).…”
Section: Introductionmentioning
confidence: 99%